Trends in the number of patients with cutaneous melanoma and their Breslow thicknesses between 2000 and 2018: A tertiary hospital-based study in İstanbul - Zehra Tacizer Kılınç; Şirin Yaşar; Pembegül Güneş; Fatih Göktay (Galenos Publishing House, 2023)
Background and Design: The global incidence of cutaneous melanoma is increasing. Breslow thickness has been reported to have decreased in recent years, in contrast to this increase. This study aims to determine annual changes in the number of diagnosed cutaneous melanoma cases and their Breslow thicknesses in our hospital. Materials and Methods: Pathology reports from cutaneous melanoma patients admitted to our hospital's dermatology clinic between 2000 and 2018 were reviewed retrospectively. Results: The study included 210 cases, 122 (58.1%) of which were male and 88 (41.9%) of which were female. The mean age of the cases was 61.08+-17.07. The year and the number of cases seen each year had a statistically significant positive correlation (p=0.003; ρ=0.640). The number of reported cases has risen over time. The year had a statistically significant negative correlation with case Breslow thicknesses (p<0.001; ρ=-0.292). The cases' Breslow thickness decreased over time. Conclusion: Our study found that as the incidence of cutaneous melanoma has increased, the Breslow thickness of cases diagnosed in recent years has decreased. These findings suggest that awareness of cutaneous melanoma has increased over time in the population served by our hospital, and the diagnostic methods and algorithms used by physicians have aided in earlier detection of the disease. However, there are still a significant number of thick cutaneous melanoma lesions, implying that more emphasis should be placed on awareness-raising activities, disease screening programs, and in-service training to detect these lesions earlier.